Strategies to enlarge the market availability of Green Building Materials (GBM) for construction works: gathering the "low-hanging fruits" / Natasha Khalil ... [et al.] - Khalil, Natasha; Ismail, Nur Adlina; Abdullah Sani, Suwaibatul Islamiyah; Mohd Nordin4, Noor Akmar Shah; Husin, Husrul Nizam (2022)
Construction sector has contributing directly or indirectly to the environmental issues. Thus, green buildings should be start with selection and usage of green building materials with better features than conventional building materials. Ideally, a careful selection of green building materials might be the fastest method for construction companies to start integrating sustainable design concepts into buildings. Despites of its benefits, the green building implementation still low in the Malaysian construction sectors due to many barriers from different aspects. Therefore, this paper aims to identify the strategies that are important for promoting green building materials (GBM) as the key catalyst to enlarge the market for construction works, or known as "low-hanging fruits" strategies. Empirical data were retrieved through a questionnaire survey with 160 construction enablers and practitioners who have experience in handling green projects. The analysis results validated the importance of all of the eight (8) "low-hanging fruit" strategies used for the study. Green procurement adoption, awareness through green training modules and harmonised information on cost and benefits of GBM were identified as the top three strategies that helps to enlarge GBM in market availability. The research findings provide a valuable reference to assist the enablers, practitioners and policy makers in developing practical strategies in enlarging the market availability of GBM adoption in construction works. Future research will investigate the tangible and intangible criteria among the strategies and their impacts on the GBM adoption process.